Report on vocational education and training 2017 - (:unkn) unknown (My University, 2017)
"The Report on Vocational Education and Training is published annually and informs about current developments on the training market. It outlines the Federal Government's priorities in the field of vocational training policy and provides information about major activities and programmes." (Editor, BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; G 1.3.1.1 Ausbildungsstellenmarkt; S 1.3.1 Ausbildung im Dualen System; G 2.2.1 Technologisierung; Berufsbildungsbericht; Ausbildungsstellenmarkt; Berufsbildungsstatistik; Berufsbildungspolitik; Berufsausbildung; Programm; Soziale Teilhabe; Digitalisierung; Berufliche Weiterbildung; Durchlässigkeit im Bildungssystem; Internationale Zusammenarbeit; Quantitative Angaben; Prognose